More milk zuri? - Wolfson, Eliza (Centre for Tropical Livestock Genetics and Health, 2019)
This comic book is aimed at primary aged children and features Zuri, a cow living in an African village who makes the creamiest milk in all the land. The story follows Zuri on her quest to learn how genetics can help her have daughters that produce enough milk to feed all the children in her village. The story introduces the concepts of genetic selection and how environment and management also play an important part in livestock productivity. With lots of colourful images and a clever mix of science, storytelling and humour.